Aphelocheirus narumonae sp.n., second species of the subgenus Micraphelocheirus Hoberlandt & Štys, 1979 (Hemiptera: Aphelocheiridae) from Thailand - Zettel, Herbert; Rattanachan, Kaewpawika (Zootaxa, 2020)
Aphelocheirus (Micraphelocheirus) narumonae sp.n. from northeastern Thailand is described. Collections of the new species originate from Khao Yai National Park and its surroundings. The new species is similar and probably closely related to Aphelocheirus (Micraphelocheirus) brevirostris Polhemus & Polhemus, 1989, an endemic species from northern Thailand. Differences are found mainly in the male genitalia and sculpture of the head and pronotum. A key to the species of Micraphelocheirus is provided.